2014
DOI: 10.1038/srep04805
|View full text |Cite
|
Sign up to set email alerts
|

DJ-1 contributes to adipogenesis and obesity-induced inflammation

Abstract: Adipose tissue functions as an endocrine organ, and the development of systemic inflammation in adipose tissue is closely associated with metabolic diseases, such as obesity and insulin resistance. Accordingly, the fine regulation of the inflammatory response caused by obesity has therapeutic potential for the treatment of metabolic syndrome. In this study, we analyzed the role of DJ-1 (PARK7) in adipogenesis and inflammation related to obesity in vitro and in vivo. Many intracellular functions of DJ-1, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…Although it has not been described, we hypothesize that as occurs with leptin, this adipokine may be increasingly secreted during the development of obesity, and probably part of this secretion occurs through EVs as validated by immunoblot in the present research. Other interesting proteins, related to obesity, were also identified in the pathological vesicles of our analysis such as protein/nucleic acid deglycase DJ-1, involved in adipogenesis and obesity-induced inflammation [47], PPIB, an adipogenic factor implicated in obesity [30], or tenascin, involved in obesity via visceral adipose tissue inflammation representing a link with extracellular matrix (ECM) remodeling [48].…”
Section: Despite the Recent Up Surge Of Extracellular Vesicles Revealmentioning
confidence: 89%
See 1 more Smart Citation
“…Although it has not been described, we hypothesize that as occurs with leptin, this adipokine may be increasingly secreted during the development of obesity, and probably part of this secretion occurs through EVs as validated by immunoblot in the present research. Other interesting proteins, related to obesity, were also identified in the pathological vesicles of our analysis such as protein/nucleic acid deglycase DJ-1, involved in adipogenesis and obesity-induced inflammation [47], PPIB, an adipogenic factor implicated in obesity [30], or tenascin, involved in obesity via visceral adipose tissue inflammation representing a link with extracellular matrix (ECM) remodeling [48].…”
Section: Despite the Recent Up Surge Of Extracellular Vesicles Revealmentioning
confidence: 89%
“…Elevated in vesicles from oleic acid hypertrophied adipocytes are other proteins of interest in relation to adipose tissue and obesity, such as PARK7/DJ-1 and MMP-14. DJ-1 protein is implicated in oxidative stress regulation among other functions, but has been also described as participating in adipogenesis and in obesity-induced inflammation [47]. Furthermore, MMP-14 was found to be overexpressed in obese adipose participating in abnormal lipid metabolism and insulin resistance [28].…”
Section: Despite the Recent Up Surge Of Extracellular Vesicles Revealmentioning
confidence: 99%
“…It has been shown that DJ‐1 expression is reduced in the pancreatic islets of patients with type II diabetes mellitus (Jain et al ., ). Furthermore, DJ‐1‐deficient mice neurons exhibit a significantly higher sensitivity to energy metabolism impairment compared to controls (Pisani et al ., ), and decreased DJ‐1 expression in 3T3‐L1 cells results in reduced adipogenesis and inflammatory cytokine expression (Kim et al ., ). These studies suggest that there may be a possible link between parkin, PINK1 and DJ‐1 and cellular metabolism, and that defects in pathways associated with metabolism could also potentially lead to PD.…”
Section: Direct and Indirect Interactions Between Parkin Pink1 And Dj‐1mentioning
confidence: 97%
“…Macrophages with DJ-1 deficiency showed downregulation of NF-κB-targeted pro-inflammatory cytokines in vitro . 24 Additionally, our recent study has demonstrated that DJ-1 is a pivotal modulator in triggering inflammatory response by targeting NADPH oxidase-mediated reactive oxygen species (ROS) generation and subsequently enhancing the secretion of pro-inflammatory cytokines, such as IL-6 and TNF- α , which are well known to promote LPC proliferation. 6, 25 However, whether DJ-1 could stimulate LPC proliferation by modulating the inflammatory and fibrosis microenvironment remains elusive.…”
mentioning
confidence: 99%